2004
DOI: 10.1089/acm.2004.10.1009
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Extract Inhibits β-Amyloid Peptide–Induced Cytokine and Chemokine Expression in Cultured THP-1 Monocytes

Abstract: The findings suggest that GE may be useful in delaying the onset and the progression of neurodegenerative disorders involving chronically activated microglial cells in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Recent studies of natural products with anti-inflammatory activity have been reported, and many of them had been done using macrophage-like cell lines, RAW264.7 cells 8,10,16,[26][27][28] and THP-1 cells. 11,13) However, we chose human colon carcinoma cells for screening because we were focusing on anti-inflammatory compounds in dietary products which might be effective through the mucosal immune response. CoLoTC cells showed a good response to LPS treatment and marked induction of IL-8 expression and production due to significant expression of TLR4 and the MD-2 gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of natural products with anti-inflammatory activity have been reported, and many of them had been done using macrophage-like cell lines, RAW264.7 cells 8,10,16,[26][27][28] and THP-1 cells. 11,13) However, we chose human colon carcinoma cells for screening because we were focusing on anti-inflammatory compounds in dietary products which might be effective through the mucosal immune response. CoLoTC cells showed a good response to LPS treatment and marked induction of IL-8 expression and production due to significant expression of TLR4 and the MD-2 gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-has been identified as the major cytokine mediator in the expression of endotoxicity. 6) LPS-treated culture cells have been used to evaluate the anti-inflammatory effects of various materials, including folk medicines such as Polygonum tinctorium, 7) Cyperus rotundus, 8) Semecarpus anacardium, 9) Ginkgo biloba, 10) and Cryptolepis buchanani, 11) and natural foods such as turmeric, 12) ginger, 13) chicory, 14) and green tea. 15) Although the mechanisms of the anti-inflammatory effects of those materials are different, a wellknown mechanism has been described as inhibition of NF-B activation and NO production caused by antioxidant active compounds.…”
mentioning
confidence: 99%
“…Traditionally, it has been used in Ayurvedic and Chinese medicine to treat asthma, diabetes, nausea, stroke, rheumatism and toothache (Afzal et al, 2001;Ali et al, 2008). Several constituents of ginger, especially gingerols and shogaols, have demonstrated potent antiinfl ammatory actions in vitro through the inhibition of cyclooxygenase 1 and 2 (Koo et al, 2001;Lantz et al, 2007;Nurtjahja-Tjendraputra et al, 2003;Tjendraputra et al, 2001), leukotriene synthesis (Kiuchi et al, 1992) and pro-infl ammatory cytokines (Grzanna et al, 2004;Tripathi et al, 2008). Thus, pharmacologically active components of ginger may mimic dual-action non-steroidal antiinfl ammatory drugs (NSAIDS).…”
Section: Introductionmentioning
confidence: 99%
“…Some natural products have been reported to suppress inflammatory processes by inhibiting the production of TNF-α and IL-1β. In this regard, ginger extract has been demonstrated to inhibit proinflammatory cytokine (TNF-α, IL-1β) and cyclooxygenase-2 enzyme expression in TNF-α-, IL-1β, or lipopolysaccharide-induced THP-1 cells [23]. Our data show that TNF-α gene was markedly upregulated after cisplatin injection and that GEO administration inhibited TNF-α mRNA expression level at all the tested doses, suggesting that the reno-protective effect of GEO may be attributable to inhibition of pro-inflammatory cytokines, such as TNF-α and IL-1β.…”
Section: Discussionmentioning
confidence: 99%